A new stripe rust resistance gene transferred from Thinopyrum intermedium to hexaploid wheat (Triticum aestivum) - Luo, Pei-Gao; Hu, Xue-Yun; Chang, Zhi-Jian; Zhang, Min; Zhang, Huai-Qiong; Ren, Zheng-Long (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2009)
Wheat stripe rust (Puccinia striiforis f. sp. tritici) races CYR31 and CYR32, prevalent in China, are virulent to many wheat stripe rust resistance genes (Yr genes). To expand the availability of effective resistance to CYR31 and CYR32, stripe rust resistance was transferred from intermediate wheatgrass (Thinopyrum intermedium) to common wheat (Triticum aestivum). The susceptible wheat cultivar CM107 was crossed with amphiploid TAI7047, derived from the wide cross Taiyuan768/Thinopyrum intermedium//76(64). Two wheat lines originating from the cross, YU24 and YU25, were resistant to CYR31 and CYR32. Pedigree analysis showed that the resistance to stripe rust in YU24 and YU25 originated from intermediate wheatgrass. Genetic analyses indicated that the resistance to stripe rust is controlled by a single dominant gene. Allelic tests determined that the resistance gene(s) in YU24 and YU25 are identical. The new gene has temporarily been designated as YrYU25. SSR and RAPD analyses showed that YrYU25 was introduced by cryptic translocation into common wheat.